Carbohydrate, lipid, bone and inflammatory markers in HIV-positive adolescents on antiretroviral therapy and hormonal contraception - Nadia Kancheva Landolt; Torsak Bunupuradah; Jullapong Achalapong; Pope Kosalaraksa; Witaya Petdachai; Chaiwat Ngampiyaskul; Sasiwimol Ubolyam; Narukjaporn Thammajaruk; Stephen Kerr; Jintanat Ananworanich (Elsevier, 2017)
Background: Little is known about the cumulative effect of HIV antiretroviral therapy (ART) and hormonal contraception (HC) on metabolism and inflammation in HIV-positive women. Methods: We conducted a cross-sectional assessment of markers for carbohydrate, lipid, bone metabolism, inflammation and coagulation in HIV-positive adolescents on ART and HC (n=37) versus on ART only (n=51) in Thailand. The Wilcoxon rank-sum test was used to assess differences between groups. Results: The median age was 19.5 years. Most adolescents (95%) were perinatally infected. All were on ART for a median of 9 years. HC used was progestin only (n=21); combined oral contraceptive (COC) tablets (n=6) for the whole study period or alternating between progestin only and COC (n=10). Prevalence of any metabolic abnormalities was 99%. Four biomarkers were significantly higher with HC vs no HC: insulin (10.3 vs 6.2μU/mL, P=0.002), insulin resistance (1.89 vs 1.19 mass units, P=0.005), 25-OH vitamin D (33.2 vs 20.2ng/mL, P<0.0001) and C-terminal telopeptide (690 vs 530ng/L, P=0.011). Triglycerides and D-dimer were significantly lower with HC (103 vs 139mg/dL, P=0.014 and 140 vs 155ng/mL, P=0.003, respectively). There was no relationship between the type of HC or ART and the above differences. Conclusion: Perinatally infected HIV-positive adolescents on ART in this pilot study had a high prevalence of metabolic abnormalities. Bone turnover markers and insulin resistance were significantly higher with HC. Research on the cumulative effect of HIV, ART and HC on metabolism and inflammation in adolescents with HIV is important in order to devise strategies for preventing and mitigating long-term comorbidities.